The Busier the Better: Greater Busyness Is Associated with Better Cognition - Festini, Sara B.; McDonough, Ian M.; Park, Denise C. (Frontiers in Aging Neuroscience, 2016)
Sustained engagement in mentally challenging activities has been shown to improve memory in older adults. We hypothesized that a busy schedule would be a proxy for an engaged lifestyle and would facilitate cognition. Here, we examined the relationship between busyness and cognition in adults aged 50-89. Participants (N = 330) from the Dallas Lifespan Brain Study completed a cognitive battery and the Martin and Park Environmental Demands Questionnaire (MPED), an assessment of busyness. Results revealed that greater busyness was associated with better processing speed, working memory, episodic memory, reasoning, and crystallized knowledge. Hierarchical regressions also showed that, after controlling for age and education, busyness accounted for significant additional variance in all cognitive constructs—especially episodic memory. Finally, an interaction between age and busyness was not present while predicting cognitive performance, suggesting that busyness was similarly beneficial in adults aged 50-89. Although correlational, these data demonstrate that living a busy lifestyle is associated with better cognition.